Predictive value of neutrophil to lymphocyte ratio, lymphocyte to monocyte ratio and mean platelet volume for pelvic inflammatory disease - AKDENİZ, ESRA (7847050 CANADA INC, 2019)
Purpose: The aim of this study was to investigate the efficacies of neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR) and mean platelet volume (MPV) as early markers in patients with pelvic inflammatory disease (PID) compared with healthy women. Materials And Methods: The study included 48 patients diagnosed with PID and 50 healthy individuals. NLR, LMR and MPV values were compared between patients with MD and the control group. Results: NLR, LMR and MPV were found to be significantly different in patients with PID when compared to healthy women (p<0,005). Conclusion: To our knowledge, this study is the first to assess the role of LMR as an inflammatory marker in patients with PID. Both NLR, LMR and MPV may he considered as useful markers of PID. Content: A retrospective controlled study to evaluate and demonstrate the predictive value of NLR, LMR and MPV measurements in diagnosis of PID.
Keywords: Pelvic inflammatory disease; Neutrophil; Lymphocyte; Monocyte; Mean platelet volume; C reactive protein; Erythrocyte sedimentation rate; Diagnosis; C-REACTIVE PROTEIN; MARKER; ROC